Downscaling reverse osmosis for single-household wastewater reuse: towards low-cost decentralised sanitation through a batch open-loop configuration - Davey, Christopher J.; Thomas, Navya; McAdam, Ewan (IWA Publishing, 2022)
There is a significant demand for water recycling in low-income countries. However, wastewater infrastructure is primarily decentralised, necessitating the development of affordable household-scale reclamation technology. In this study, a batch open-loop reverse osmosis (RO) system is therefore investigated as a low-cost clean water reclamation route from highly saline concentrated blackwater. In a single-stage configuration, increasing feed pressure from 10 to 30 bars improved selective separation at water recovery exceeding 85%, whereas lower cross-flow velocity improved product recovery, reducing specific permeate energy demand from 21 to 4.8 kWh m−3. Rejection achieved for total phosphorous (99%), chemical oxygen demand (COD, 96%), and final pH (8.7) of the RO permeate was compliant with the ISO30500 reuse standard for discharge. However, the rejection of total nitrogen in the RO permeate was non-compliant with the reuse standard due to the transmission of low-molecular weight (MW) uncharged organic compounds. It is suggested that rejection may be improved by increasing feed pressure to rebalance selectivity but may also be controlled by reducing fluid residence time (storage) to constrain the hydrolysis of urea. The economic analysis identified that a high-pressure 1812 element cost of ∼US$30 meets the sanitation affordability index of US$0.05 capita−1 day−1. However, the unit cost of a high-pressure feed pump must be reduced to ∼US$500 to obtain an affordable system cost. These unit costs can be achieved by manufacturing 1812 elements at economies of scale, and by adopting pumping solutions that have been developed for other applications requiring high pressures and low flows. Overall, our findings suggest that RO in the batch open-loop configuration has the potential to deliver affordable and safe water production from blackwater in a decentralised (single-household) context.
Keywords: batch RO; blackwater; decentralised RO; urine and faeces; wastewater RO